The Origin of Novel Flavonoids in Phlox Allotetraploids - Levy, Morris (1971)
The flavonoids of two diploid species of Phlox and two of their allotetraploid derivatives were characterized. The tetraploids accumulate five flavonoids not observed in the parental species. Generally, novel compounds are less highly glycosidated than, but otherwise similar to, parental compounds that they partially or totally replace. We propose that hybridity and polyploidy have repressed or suppressed the activity of certain ancestral genes responsible for the production of glycosidating enzymes. Accordingly, the novel compounds are merely the accumulated or modified precursors of parental compounds.